Laparoscopic partial nephrectomy in rats - Meyer,Fernando (2007)
PURPOSE: To establish an experimental model of laparoscopic partial nephrectomy (LPN) in rats and to analyze morphological alterations in the renal parenchyma utilizing an electric cautery and harmonic scalpel. METHODS: Forty Wistar rats were used, divided in 2 experiments with 20 rats each: experiment I, LPN was performed with an electric cautery and the rats were subdivided into groups A and B; experiment II, LPN was performed with a harmonic scalpel and they were subdivided into groups C and D. The animals in groups A and C were sacrificed shortly after surgery and the remnant kidney was removed to study the following variables: necroses and degeneration. In groups B and D a laparatomy was performed for retrieval of the remnant kidney on the 14th day after surgery to analyze fibrous scarring. RESULTS: For the variables necroses and fibrous scarring, the electric cautery creates, on average, greater width than that produced by the harmonic scalpel (p=0.0002 and p=0.0068 respectively). Regarding the variable of degeneration, we found no significant difference between the two types of scalpels (p=0.1267). CONCLUSIONS: LPN in rats is an adequate and feasible experimental model. The electric cautery caused greater damage to remnant renal tissue when compared to harmonic scalpel.